China's Maritime Silk Road Initiative: A quest for sea power - Hlongwa, Lungani Nelson (Scientia Militaria - South African Journal of Military Studies, 2020)
Much has been written about China’s deep ambitions as the country moves towards great power status. The Maritime Silk Road Initiative (MSRI) is just one example of how China is flexing its muscles, and if history is to be believed, there is a strong correlation between maritime success and national economic prosperity. The study,  on which this article reports, examined China’s MSRI through the lens of sea power theory. It was argued that the New Silk Road, which will most likely be backed by a modern blue-water navy, could represent a new era of maritime supremacy. However, to see the MSRI as a pursuit of sea power requires an understanding of how maritime logistics functions as power. The seamless movement of goods across the ocean is at the heart of the MSRI. Therefore, the research question that was pursued related to how maritime logistics functions as a tool for power projection. Although sea power theory recognises merchant shipping as a core element of sea power, it was further argued that scholarly work in critical logistics and mobility studies could enhance our understanding of logistical power. The study therefore aimed to conceptualise the MSRI through the lens of sea power by highlighting maritime logistics as a strategic conduit for power projection.